Toxicity of photodynamic therapy with LED associated to Photogem (R): An in vivo study - Trindade, Flavia Zardo; Pavarina, Ana Claudia [UNESP]; Dias Ribeiro, Ana Paula; Bagnato, Vanderlei Salvador; Vergani, Carlos Eduardo [UNESP]; de Souza Costa, Carlos Alberto [UNESP] (Springer London Ltd, 2012)
The aims of this study were to evaluate the effects of PhotogemA (R)-mediated photosensitization on rat palatal mucosa and the biodistribution of the photosensitizer in this tissue. A solution of PhotogemA (R) (500 or 1000 mg/l) was applied to the palatal mucosa for 30 min and the exposure time to blue LED (460 nm) was 20 min (144 J/cm(2)). At 0, 1, 3, and 7 days, palatal mucosa was photographed for macroscopic analysis. After killing, the palate was removed for microscopic analysis. Thermal mapping evaluated temperature change in the tissue during irradiation. All experimental groups revealed intact mucosa in the macroscopic analysis. Tissue alterations were observed microscopically for only four out of 80 animals subjected to PDT. Fluorescence emitted by PhotogemA (R) was identified and was limited to the epithelial layer. A temperature increase from 35 to 41A degrees C was recorded. PhotogemA (R)- mediated PDT was not toxic to the rat palatal mucosa.
Keywords: Photodynamic therapy; Toxicity; Rats; Oral mucosa; Fluorescence microscopy